Tris(pyrazolyl)methane molybdenum tricarbonyl complexes as catalyst precursors for olefin epoxidation - Gomes, Ana C.
The molybdenum tricarbonyl complexes [Mo(CO)(3)(HC(3,5-Me(2)pz)(3))] (1) and [Mo(CO)(3)(HC(pz)(3))] (2) (HC(3,5-Me(2)pz)(3) = tris(3,5-dimethyl-1-pyrazolyl)methane, HC(pz)(3) = tris(1-pyrazolyl)methane) were obtained in good yields by the microwave-assisted reaction of Mo(CO)(6) with the respective organic ligand. Complete oxidative decarbonylation of 1 and 2 was achieved by reaction with excess tert-butylhydroperoxide (TBHP) in 1,2-dichloroethane at 55 degrees C. For complex 1, the (mu(2)-oxo)bis[dioxomolybdenum(VI)] hexamolybdate of composition [{MoO2(HC(3,5-Me(2)pz)(3))}(2)(mu(2)-O)][Mo6O19] (3) was obtained in good yield, and its structure was determined by single crystal X-ray diffraction. The compound (4) obtained by oxidative decarbonylation of 2 was not unambiguously identified, but may be chemically analogous to 3. Compounds 1-4 were examined for the first time as homogeneous (pre)catalysts for the epoxidation of olefins with TBHP, using different types of cosolvents at 55 degrees C. During the catalytic reactions 1 and 2 transform in situ into 3 and 4, respectively, and the latter two are fairly stable catalysts. Catalytic tests and characterization studies of the recovered catalysts were carried out in an attempt to understand the kinetic differences observed between the compounds prepared in situ during the catalytic reaction and those prepared prior to the catalytic reaction, from the same precursor complex. (c) 2013 Elsevier B.V. All rights reserved.